2022
DOI: 10.1002/jaba.946
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mastery criteria applied to individual targets and stimulus sets on acquisition of tacts, intraverbals, and listener responses

Abstract: Mastery criteria can be applied to individual targets or stimuli organized into sets. Wong et al. (2021) and Wong and Fienup (2022) found that participants who received special education services learned sight words more rapidly when an individual target mastery criterion was applied. The current study replicated and extended these findings across novel skills. Five participants with ASD received tact or intraverbal training in Experiment 1, and 2 participants with ASD received auditory–visual conditional disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…This study systematically replicated the set size manipulations conducted by Kodak et al ( 2020 ) and Vladescu et al ( 2021 ) research with operant analysis (OA) acquisition criterion (Cordeiro et al, 2022 ; Wong et al, 2022 ; Wong & Fienup, 2022 ). The results showed that the set-size-3 condition was consistently more efficient than the set-size-12 in terms of acquiring new operants prior to and post the adjustment of the instructional trials and duration, which is consistent with Vladescu et al’s findings.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This study systematically replicated the set size manipulations conducted by Kodak et al ( 2020 ) and Vladescu et al ( 2021 ) research with operant analysis (OA) acquisition criterion (Cordeiro et al, 2022 ; Wong et al, 2022 ; Wong & Fienup, 2022 ). The results showed that the set-size-3 condition was consistently more efficient than the set-size-12 in terms of acquiring new operants prior to and post the adjustment of the instructional trials and duration, which is consistent with Vladescu et al’s findings.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, we implemented an operant analysis (OA) acquisition criterion (Cordeiro et al, 2022 ; Kim et al, 2023 ; Wong et al, 2022 ; Wong & Fienup, 2022 ) that targeted the acquisition mastery of individual operants instead of set-based acquisition criteria as used by Kodak et al ( 2020 ) and Vladescu et al ( 2021 ). Most studies focusing on skill acquisition implemented set-based analysis in which researchers randomized blocks of trials that consisted of multiple operants and presentations of each antecedent (Wong et al, 2022 ) and evaluate acquisition criteria based on the percentage of trials with independent correct responses across all responses emitted in a session (Grow et al, 2011 , 2014 ; Grow & Van der Hijde, 2017 ).…”
mentioning
confidence: 99%
“…Our study contributed to bridging acquisition‐criterion and intervention‐dose research. Prior studies either solely focused on the instructional arrangement (Cordeiro et al, 2022; Wong et al, 2021; Wong & Fienup, 2022) or dose parameters (Neil & Jones, 2015, 2019; Roxburgh & Carbone, 2013). The current study directly compared set and operant analysis conditions as well as different levels of trial dosage (12 and 20 trials).…”
Section: Discussionmentioning
confidence: 99%
“…The figure depicted in the Supporting Information shows the cumulative number of words acquired for Dyad 1 (Dylan and Tim) and Dyad 2 (Bob and Jill) across sessions. We included this graph because the analysis of data per session is in accordance with previous research on this topic (e.g., Cordeiro et al, 2022;Wong et al, 2021;; however, those data of the prior researchers ignore that sessions were not equal between conditions. That is, two conditions were composed of 20 trials (Set Analysis 5 and Operant Analysis 5) and one condition was composed of 12 trials (Operant Analysis 3).…”
Section: Baseline and Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation